Impact of fasting on human health during Ramadan - Shah, Junaid Ali; Rahman, Mujeeb Ur; Abdikaxarovich, Sidikov Akmal; Sikandar, Prince; Yerian, Abduvaliyev Dikhanbay (International Journal of Public Health Science (IJPHS), 2023)
Ramadan fasting is a religious practice observed by millions of Muslims worldwide. Firstly, the experimental studies were searched on different websites like PubMed, Science direct, and google scholar to find out the latest research regarding Ramadan fasting. Studies have shown that Ramadan fasting influences body weight, blood glucose, insulin, lipid levels, and blood pressure. However, the effects of fasting on mental health and specific health conditions such as cardiovascular diseases, cancer or metabolic disorders vary depending on individual factors. Because, fasting duration, the presence of chronic diseases, and obesity are all factors that can alter the outcomes. Until now, Multiple studies on Ramadan fasting's impact on health have been conducted but certain limitations make the results inconclusive. We hope to gain a better understanding of the potential benefits and risks associated with this religious practice. Ultimately, this knowledge can be used to inform healthcare professionals and individuals who are participating in Ramadan fasting. Further research is necessary to explore underlying mechanisms and optimize fasting protocols for chronic disease patients. Overall, this review emphasizes the need for further research on the effects of Ramadan fasting on human health and its potential as a tool for improving health outcomes in diverse populations.